Keladi candik (Alocasia longiloba Miq.) petiole extracts promote wound healing in a full thickness excision wound model in rats - Che Hamzah, Nurul Hazirah; Mohammed, Arifullah; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Asari, Mohd Asnizam; Hamzah, Zulhazman; Shaik, Ibrahim Khalivulla (Hainan Medical University, 2019)
Objective: To investigate the wound-healing effect of Alocasia longiloba (A. longiloba) petiole extract on wounds in rats. Methods: Twenty-two male Sprague-dawley rats were randomly assigned to receive 10% solcoseryl gel, phosphate buffer saline, 50% ethanol, 95% ethanol and hexane extracts of A. longiloba at 1.5%, 3% and 6% doses, respectively. A full thicknesses wound (6 mm) was created on the dorsal of the rat; and all rats were applied with the extract solutions, 10% solcoseryl gel and phosphate buffer saline once a day topically until day 12. The wound was photographed on day 1, 6 and 12, and the percentage of wound contraction was calculated. On day 12, rats were sacrificed and histological examination of granulation tissue was carried out using haematoxylin & eosin and Masson’s Trichrome stain to determine the wound healing effect. Results: In this study, 6% of 50% and 95% ethanol extracts of A. longiloba showed 82.50% and 82.32% wound contraction, respectively, and were comparable with 10% solcoseryl gel (82.30%). Meanwhile, phosphate buffer saline treated group showed the lowest wound contraction (69.86%). Histological assessment of wound treated with 6% of 95% ethanol extract of A. longiloba showed distinct epidermal and dermal layer, higher proliferation of fibroblast and more angiogenesis with collagen compared to other wound treated groups. Conclusions: A. longiloba petiole extracts have a wound healing potential and 6% of 95% ethanol extract of A. longiloba is more effective. Further studies are required to understand the wound healing mechanism of action of the extract.